Pulmonary Hypertension in an Elderly HIV-infected Veteran Population - Jessica, A Smith; Palak, Shah; Rahul, Khosla; Angelike, P Liappis (Journal of Clinical Research In HIV AIDS And Prevention, 2016)
Pulmonary hypertension may occur as a co-morbid disease in HIV. We examined the characteristics of our HIV infected veterans with pulmonary hypertension and compared them with a control group of HIV infected patients without pulmonary hypertension. Among our cohort, patients were diagnosed with pulmonary hypertension at a mean age of 49.8 y ± 11.0y. This diagnosis came about 8.1y ± 6.7y after the diagnosis of HIV. Our pulmonary hypertension patients lived for about 3.4 ± 3.0y after their pulmonary hypertension diagnosis. The presence of pulmonary hypertension in HIV infection confers an increased risk of mortality. Mortality in our pulmonary hypertension cohort was 73%.
Keywords: pulmonary heart disease; pulmonary hypertension; HIV; AIDS; mortality; age